(3OjhGf Ydj Hf CHj WGdH cQe Gddg hLggs - (3GdgGTej, GdbQTj, CHh GdMSf, Ydj Hf CHj WGdH Hf YHO GdeWdH, J (B40 (3gs ((3YeQ Hf jhSa YTi JcI GdMGJejs)
(3ChdgG (B:s
(3MQa GdCda(B: (3GdfGS ef LgI GdJeKGd CcaGA (B*** (3CHhge BOe hGdCe MhGA , aEf jcf dge aj CUdge TQa (B*** (3jaGNQhf Hg aGdWjf hGdeGAs
(3BNQgG (B:s
(3eeG hUaJ CSCdc Cf JUdj Ydi SjOfG eMeO hBd eMeO hCf dG JMQefG TjFG eeG SCdfGc hROfG ef aVdc Efc Ydi cd TjA bOjQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe(B: 4 / 295s
(3eYLe GdeDdajf(B: 2 / 452s
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdbWQjIs
(3ehGUaGJ GdhYGA (B:s
Keywords: (3GdCOHs